MINAT SISWA SMK KELAS XII PROGRAM KEAHLIAN TEKNIK INSTALASI TENAGA LISTRIK MASUK PERGURUAN TINGGI DITINJAU DARI FAKTOR INTERNAL DAN EKSTERNAL DI SMK NEGERI 2 LANGSA - Hari Anna Lastya (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
This research aims to discern the interest and to identify the contribution of internal and external factors of Electrical Engineering Installation Power Vocational Program of XII students at State Vocational High School (SMKN) 2 Langsa to continue to university level. This research is a quantitative descriptive research. The research subjects were students 51 students of class XII Electrical Engineering Installation Power Vocational Program at SMK Negeri 2 Langsa. Data was collected by using questionnaire by using validity construction that have been prepared to experts (expert judgment) and the factor analysis method. Instrument reliability tests were calculated by means of internal consistency by using the Alpha formula. The amount of interest analyzed by the descriptive method and the factors that influence the interest to enter higher education are tested statistically by multiple regression with the help of SPSS version 22. The results of the questionnaire data show that students’ interest in countinuing to university from internal factors and external factors in SMK Negeri 2 Langsa had 73.81% average mean score. Interest in university entrance had 74.31% mean score and internal factors had the average percentage of 79.42% mean score and are categorized as high score. External factors had 69.06% mean score and categorized as high too. The relationship between internal factors with the interest for university entrance is very strong, with a 0.624 correlation coefficient score. Meanwhile, internal factors are the most influencing factors, namely the regression coefficient of 0.295 and external factors with a regression coefficient of 0.113 contributing to student interest for university entrance.